2008
DOI: 10.1113/jphysiol.2007.148304
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neural KCNQ channels: signalling pathways, structural motifs and functional implications

Abstract: Neural M-type (KCNQ/Kv7) K + channels control somatic excitability, bursting and neurotransmitter release throughout the nervous system. Their activity is regulated by multiple signalling pathways. In superior cervical ganglion sympathetic neurons, muscarinic M 1 , angiotensin II AT 1 , bradykinin B 2 and purinergic P2Y agonists suppress M current (I M ). Probes of PLC activity show agonists of all four receptors to induce robust PIP 2 hydrolysis. We have grouped these receptors into two related modes of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
167
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(174 citation statements)
references
References 98 publications
4
167
1
2
Order By: Relevance
“…Several mechanisms previously described for agonist-induced suppression of neuronal M-currents could potentially operate in vascular myocytes (e.g. depletion of plasma membrane phosphatidylinositol 4,5-bisphosphate (36 -40), or elevation of cytosolic [Ca 2ϩ ]) (16,41). Our previous findings, however, strongly support involvement of PKC, a less commonly proposed regulator of M-currents (42,43), in the suppression of endogenous Kv7 currents by physiologically relevant concentrations of AVP.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Several mechanisms previously described for agonist-induced suppression of neuronal M-currents could potentially operate in vascular myocytes (e.g. depletion of plasma membrane phosphatidylinositol 4,5-bisphosphate (36 -40), or elevation of cytosolic [Ca 2ϩ ]) (16,41). Our previous findings, however, strongly support involvement of PKC, a less commonly proposed regulator of M-currents (42,43), in the suppression of endogenous Kv7 currents by physiologically relevant concentrations of AVP.…”
Section: Discussioncontrasting
confidence: 40%
“…Kv7 voltage-activated potassium channels are expressed in many excitable cell types, including neurons, cardiac, skeletal, vascular, and visceral myocytes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) where they function to stabilize resting membrane potential and restrict cellular excitability (6,16). The five members of the Kv7 family (Kv7.1-Kv7.5) are encoded by five mammalian genes (KCNQ1-5), and the individual gene products assemble as homomeric or heteromeric tetramers to form functional channels (17).…”
mentioning
confidence: 99%
“…Structural studies on Kir channels (1,2,5) demonstrated that PIP 2 directly interacts with the channels. Subsequent studies supported that PIP 2 also interacts directly with voltage-gated potassium (Kv) channels (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Several positive residues that may be critical for PIP 2 activity have been identified (7,11,18,(20)(21)(22)(23)(24).…”
mentioning
confidence: 97%
“…The PLCβ enzymes play critical roles in neural functions, and PLCβ1-and PLCβ4-knockout mice develop epilepsy and ataxia, respectively (Kim et al, 1997). The G q/11 -coupled receptor-PLCβ signaling pathways contribute to neuronal functions through multiple second messengers that cause modulation of ion channels (Anwyl, 1999;Hernandez et al, 2008;Hughes et al, 2007;Suh and Hille, 2005), Ca 2+ release from internal stores (Ross et al, 2005), endocannabinoid release (Kano et al, 2009) and activation of enzymes (Amadio et al, 2006;Delmas et al, 2004). Understanding how these signaling pathways are regulated will undoubtedly lead to a better understanding of their roles in brain functions.…”
Section: Introductionmentioning
confidence: 99%